2017
DOI: 10.1007/978-3-319-57379-3_19
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and Its Impact on Quality of Life

Abstract: Sarcopenia is recognized as a major health problem among older adults. This syndrome is associated with serious health consequences in terms of frailty, disability, morbidity and mortality. The aim of this study is to review sarcopenia and its impact on quality of life (QoL). MEDLINE database was searched from January to March 2016 using predefined search terms "sarcopenia", quality of life". Based on extensive literature search, 32 articles were identified while only 6 studies met the inclusion criteria and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
132
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(159 citation statements)
references
References 18 publications
2
132
0
6
Order By: Relevance
“…Huo et al reported that the number of selfreported falls was higher in sarcopenic obese older adults than either sarcopenic or obese alone groups. 34,35 Both ageing and obesity can result in disability by leading to decreased organ function, increased chronic diseases and inflammation. 32 The present study demonstrated that the mean scores for domains of the SF-36 questionnaire were lower in both obese and sarcopenic obese participants compared to the sarcopenic and non-sarcopenic non-obese participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huo et al reported that the number of selfreported falls was higher in sarcopenic obese older adults than either sarcopenic or obese alone groups. 34,35 Both ageing and obesity can result in disability by leading to decreased organ function, increased chronic diseases and inflammation. 32 The present study demonstrated that the mean scores for domains of the SF-36 questionnaire were lower in both obese and sarcopenic obese participants compared to the sarcopenic and non-sarcopenic non-obese participants.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, a majority of the previous and recent studies measured muscle mass only for sarcopenia definition, and in addition, HR-QOL assessment was based on questionnaires that do not provide a detailed evaluation of this topic as much as SF-36. 34,35 Both ageing and obesity can result in disability by leading to decreased organ function, increased chronic diseases and inflammation. During this process, both qualitative and quantitative reduction of muscle tissue predispose patients to a weaker physical performance, chronic pain due to degeneratıon of the skeletal muscle system, imbalance and falling, and finally, older adults obtain lower scores in physical domains of HR-QOL.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that sarcopenia can have a great impact on older adults because of how it often increases the risk of adverse outcomes, such as physical disability, poor quality of life and death. [1][2][3][4][5] Sarcopenia is frequently found in patients with specific diseases, including 95% of patients after pneumonia, 6 21.8-95.0% of patients who experienced a femoral proximal fracture [7][8][9] and 53.6% of patients who have had a stroke. 6 Indeed, sarcopenia found in stroke patients has been separately classified as "stroke-related sarcopenia."…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia and undernutrition are both associated with higher care costs and several adverse health outcomes, namely poor quality of life, prolonged length of stay in hospital and mortality . Routine undernutrition identification is increasing in the clinical practice, but sarcopenia remains poorly identified.…”
Section: Introductionmentioning
confidence: 99%
“…8 This syndrome was recently pointed out as a prognostic indicator for long-term mortality in hospitalised older patients. 9 Sarcopenia and undernutrition are both associated with higher care costs 10,11 and several adverse health outcomes, namely poor quality of life, 12,13 prolonged length of stay in hospital 11,14,15 and mortality. 11,16,17 Routine undernutrition identification is increasing in the clinical practice, but sarcopenia remains poorly identified.…”
Section: Introductionmentioning
confidence: 99%